Towards an integrative job demand-resource model of job burnout and job performance : a meta-analytic path analysis - Narayanan Anand Chandrasekar (2008)
Job burnout is a syndrome of emotional exhaustion (EE), depersonalization (DP), and reduced personal accomplishment (RPA) that can occur among individuals at the workplace. Very little research has examined the inter-relationships amongst EE, DP, RPA, and their relationships with job characteristics and impact on job performance. This thesis examines three questions (a) How are the three components of burnout (EE, DP, RPA) related to job performance?, (b) How are the three components of burnout related to job demands and job resources in the job demands-resources (JD-R) model?, and (c) How are the inter-relationships between EE, DP and RPA best modeled to develop a theory of burnout that links the JD-R model with job performance? The first two questions are answered using meta-analytic correlations obtained from 229 independent samples reported in published research studies. The third question is answered by means of proposing and testing competing developmental sequences of EE, DP, and RPA that link the JD-R model with job performance using meta-analytic path analyses. This is the first study to review and conduct a meta-analysis on the burnout-job performance relationship and also the first in comparing various developmental sequences of burnout in linking the JD-R model to job performance.